The Role of Affective Control in Emotion Regulation During Adolescence - Schweizer, Susanne (Emotion, 2020)
In this review, we evaluate evidence for the hypothesis that developmental changes in emotion regulation tendencies during adolescence depend on the maturation of affective control. Affective control refers to the application of cognitive control to affective contexts, that is, the capacity to attend and respond to goal-relevant affective information, while inhibiting attention and responses toward distracting affective information. The evidence suggests that affective control develops throughout adolescence into adulthood. However, the developmental trajectory appears not to be uniform across different facets of affective control. In particular, the capacity to inhibit attention and responses to distracting affective information may be reduced during adolescence relative to childhood and adulthood. Focusing on the association between affective control and emotion regulation development in adolescence, the research reviewed supports the notion of affective control as a cognitive building block of successful emotion regulation. Good affective control appears related to fewer ruminative tendencies in adolescence as well as more frequent and successful reappraisal in older adolescents. Lower use of habitual suppression, itself a type of affective inhibition, shows an association with updating capacity. We conclude by discussing the implications of these findings for mental health and the potential mental health benefits associated with improving affective control.